The relationship between heterotrophic feeding and inorganic nutrient availability in the scleractinian coral T. reniformis under a short‐term temperature increase. (30th September 2015) - Ezzat, Leïla; Towle, Erica; Irisson, Jean‐Olivier; Langdon, Chris; Ferrier‐Pagès, Christine
Abstract: Worldwide increase in seawater temperature represents one of the major threats affecting corals, which experience bleaching, and thereafter a significant decrease in photosynthesis and calcification. The impact of bleaching on coral physiology may be exacerbated when coupled with eutrophication, i.e., increasing plankton, inorganic nutrient concentrations, sedimentation and turbidity due to coastal urbanization. Whereas zooplankton provision (heterotrophy) may alleviate the negative consequences of thermal stress, inorganic nutrient supply may exacerbate them, which creates a paradox. Our experimental study aims to disentangle the effects of these two components of eutrophication on the physiological response of Turbinaria reniformis subject to normal and to a short‐term temperature increase. Additionally, three different inorganic nutrient ratios were tested to assess the influence of nutrient stoichiometry on coral physiology: control (ambient SW 0.5 μ M N and 0.1 μ M P), N only (ambient + 2 μ M N) and N + P (ambient + 2 μ M N and + 0.5 μ M P). Our results show a deleterious effect of a 2 μ M nitrate enrichment alone (N) on coral photosynthetic processes under thermal stress as well as on calcification rates when associated with heterotrophy. On the contrary, a coupled nitrate and phosphorus enrichment (N + P) maintained coral metabolism and calcification during thermal stress and enhanced them when combined with heterotrophy. Broadly, our results shed light on the tight relationship existing between inorganic nutrient availability and heterotrophy. Moreover, it assesses the relevance of N: P stoichiometry as a determining factor for the health of the holobiont that may be adapted to specific nutrient ratios in its surrounding environment.